Pateo do Collegio: um lugar na cidade de São Paulo - Fortunato, Ivan [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
The Pateo do Collegio, at the heart of São Paulo Historic Downtown, is recognized as the founding place of the city of São Paulo. Located at the hill of the Piratininga Plateau, it was discovered in the sixteenth century by the priests of the Society of Jesus, who set school and church in the place, naming the village of São Paulo Piratininga in Mass celebrated at January 25, 1554. We have met the place by chance, when a sudden sense of enchantment led us to want to know it better. From the hypothesis that its geographicity allows us to classify it as an ontological place, this thesis aimed to uncover its essence and demonstrate the sense of this place in its historical, cultural, built, telluric and symbolic aspects. Epistemologically grounded in Humanistic Geography, we have developed our thesis by the presence in the place, observing, talking to people, drawing maps, photographing, but also checking the literature and historical records... the main intention was the gathering of meanings and values about this iconic place. In the end, this geopoetics gave us the prerogative to name the Pateo do Collegio as a living place in São Paulo, qualified by very private historicity and geographicity, as being the place where the city was born, raised and expanded, from village to metropolis...

O Pateo do Collegio, no coração do Centro Histórico paulistano, é reconhecidamente o lugar de fundação da cidade de São Paulo. Localizado no alto da colina do Planalto de Piratininga, foi descoberto no século XVI pelos padres da Companhia de Jesus, que fixaram colégio e igreja no lugar, batizando a vila de São Paulo de Piratininga, em missa celebrada no dia 25 de janeiro de 1554. Conhecemos o lugar ao acaso, quando um súbito sentido de encantamento nos motivou a querer conhecê-lo melhor. Partindo da hipótese de que sua geograficidade permite qualificá-lo como lugar ontológico, esta tese teve como propósito desvendar sua essência e demonstrar o sentido de lugar presente em seus aspectos históricos, culturais, construídos, telúricos e simbólicos. Epistemologicamente fundamentados pela Geografia Humanista, desenvolvemos nossa tese pela presença no lugar, observação, conversas, desenho de mapas, fotografias, mas, também pela literatura e registros históricos... com a intenção de reunir significados e valores desse lugar emblemático. Ao final, essa geopoética nos concede a prerrogativa de nomear o Pateo do Collegio como um lugar vivo na cidade de São Paulo, qualificado por uma historicidade e uma geograficidade muito particulares, sendo o lugar onde a cidade nasceu, permaneceu e dali expandiu-se, de vila à metrópole...
Keywords: Geografia humana; Centros históricos; Percepção geografica; São Paulo (SP) - História